The new building of the Bureau of Science, 1901-1905 - Garcia, Felino S. (2014)
This paper is a historical reconstruction of the rationale behind the renaming of the Bureau of Government Laboratories into the Bureau of Science and the construction of its new building based on Paul C. Freer’s account titled, Description of New Buildings of the Bureau of Government Laboratories, published in 1905. It is a critical reading of the scientific and modernizing project of the American colonial state in the Philppines through the Bureau of Science. The paper discusses in detail the structure and facilities of the new building and describes its reorganization including the administrative structure of its operations, as well as the establishment of laboratories in the new building. The Bureau of Science and its new building signified an inside/ outside dichotomy which differentiated the modern spaces inhabited by the colonial scientists and the uncontrolled, unsubdued tropical environment of the Filipinos. An important adjunct to the American colonial regime, the Bureau of Science reflects the extent and reach of the scientific and modernizing project of the colonial state.
Keywords: Racism; Freer, Paul C; Bureau of Science -- History; Bureau of Science -- Buildings